Digital evaluation of occlusal reduction of metal crown preparations in students in the COVID-19 era: A cross-sectional study - Khadijah M. Baik (Saudi Dental Journal)
Introduction: Occlusion of extra-coronal restorations depends on the reduction achieved during crown preparation. Ensuring adequate reduction is therefore essential for the success of the final restoration. The objective of this study was to digitally quantify the occlusal reduction performed by preclinical undergraduate dental students and to compare their performance across the year and using a hybrid teaching approach developed because of the COVID-19 pandemic. Methods: Eighty full metal crown preparations on typodonts were scanned using the KaVo Arctica 3D Optical scanner. Occlusal reduction was measured using Autodesk Fusion 360 v2.0 by superimposing an unprepared tooth over the preparation and taking measurements at six occlusal points (mesio-buccal (MB), disto-buccal (DB), mesio-lingual (ML), disto-lingual (DL), mesial fossa (MF), and distal fossa (DF)). A general linear model was used to compare student performance in the mid vs final year exams and in 2018/19 vs 2020/2021. Results: The adequacy of occlusal reduction was variable. Occlusal reductions of the MF (p = 0.014) and DF (p = 0.011) were significantly lower in the final exam than the mid-year exam in 2018/2019. There was also occlusal under-reduction at all six occlusal points in 2020/2021 compared with 2018/2019. Conclusions: Students must be encouraged to use verification guides throughout the procedure to ensure adequate reductions. These verification methods can be as simple as putty indices or as advanced as optical scanners. The use of verification methods alongside a hybrid virtual and live teaching approach may guarantee the best results.